O papel dos parques tecnológicos no estímulo e criação de spin-offs acadêmicos - Collarino, Roberto Leonardo Xavier (2014)
One witness a world in which a company, to survive in a increasingly competitive market, needs to lauch new products in a dwindling time. To reach this, the company needs to acquire technologies, knowledge, skills and abilities through the innovation in both products and processes. In this context, there are the technology parks, that are physical spaces where it happens technology, innovation and information sharing. A technology park works as a mechanism for business: there are technology-based companies, business incubators, universities, research institutions, higher education institutions and research laboratories. Thus, it creats a propitios environment so that there are relationships between companies and universities, or, in other words, academic knowledge becomes a part of the daily business and it develops itself in innovation that can be marketed. So that the park can achieve it goals and develop and disseminate technological processes it needs to establish strong links with government institutions, compnies that complies with its objective and universities that are able to provide academic knowledge. This study aims to determine whether the presence of a technology park encourages the creation and development of academic spin-offs in São Carlos city (SP). It was a multi case study in São Carlos Science Park and Parque Eco Tecnológico Damha-São Carlos. As the mainly results, it was possible to note that having two technology parks in the city was not enough to stimulate the creation of academic spin-offs, but it is enough to maintain and develop the spin-offs that already been created. Besides, it was possible to note that the entrepreneurs miss the incentive from the university to create academic spin-offs and to create links with incubators and technology parks.